GREEN HUMAN RESOURCE MANAGEMENT (GHRM) AND GREEN ENTREPRENEURSHIP (GE): A SIMPLE REVIEW - Assery, Syeh; Hassanee, Narong; Sutrisno, Totok (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
Introduction/Main Objectives: This research is aimed to explore the publication related with Green Human Resource Management (GHRM) and Green Entrepreneurship (GE) in Scopus Database. Background Problems: Many previous studies have studied GHRM and GE, but most have studied them separately or in connection with various other concepts.. Novelty: The novelty of this paper explain about GHRM and GE use simple review. Research Methods: This research method uses SIMPLE, a systematic information for manuscript preparation and literature elaboration proposed by the researcher. Simple analysis is performed to obtain the results. Finding/Results: The results found that GHRM article 88, GE article 48 found, GHRM and GE article 1 found. Conclusion: GHRM positively affected GE. Future research is needed to find better results using SLR and bibliometric analysis.